Heart Failure in Early Adulthood: A Systematic Review of Contributory Clinical and Lifestyle Factors - Vaishnavi B.; Sunil Kumar Kadiri (Current Hypertension Reviews, 2026)
Background: The rising incidence of congestive heart failure in younger adults, traditionally linked to older demographics, necessitates a thorough examination of relevant clinical and lifestyle factors. This study analyzes the factors influencing congestive heart failure in early adulthood, focusing on genetic predispositions, congenital cardiac defects, and acquired risk factors such as hypertension, diabetes, and obesity. Methods: An extensive and comprehensive literature search was undertaken across multiple scholarly databases, including PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar. The systematic review integrates findings from the selected relevant sources to provide a broad overview of the current state of knowledge in this field, distinguishing it from systematic reviews conducted in accordance with PRISMA guidelines. Results: Recent studies emphasize the interaction between genetic markers and environmental factors that contribute to the acceleration of cardiac dysfunction in younger populations. Prolonged diagnosis and insufficient screening expedite disease advancement, highlighting the essential need for early detection measures. Discussion: Various management approaches, including pharmacological interventions and lifestyle modifications, are examined with a focus on long-term outcomes. Preventive strategies, such as public health initiatives and patient education, are essential for reducing incidence rates. Conclusion: This review highlights the pressing need for targeted research and healthcare reforms to address the rising incidence of heart failure in early adulthood. Identifying key risk factors and promoting preventive strategies enable clinicians and policymakers to improve early intervention and patient outcomes.